Conservation importance of mammal fauna in Dak Rong nature reserve, Quang Tri province - Manh, Nguyen Dac; Dang, Nguyen Xuan; Nghia, Nguyen Xuan (Academia Journal of Biology, 2014)
Conservation importance of mammal fauna in Dak Rong nature reserve, Quang Tri province